Peran Bhabinkamtibmas Dalam Mecegah Paham Radikal Di Wilayah Hukum Polrestabes Bandung - Werluka, Michael Leonardo (Police Studies Review, 2020)
This research is focused on how the role of Bhabinkamtibmas in handling and preventing radical understanding in the Bandung Polrestabes area. The focus of this study is concerned as necessary since radicalism is able to jeopardise the existence of sovereignty and ideology. However, the presence of radical groups is not a concern for the leadership of Bandung Police. The issues raised in this research are: (1) What are the roles of Bhabinkamtibmas in preventing radical understanding in the Bandung Police Resort today ?; (2) What are the systems and methods of Bhabinkamtibmas in preventing radical ideas ?; (3) What are the support and inhibit factors in the role of Bhabinkamtibmas to prevent radical ideas?;This study uses a qualitative approach with descriptive methods. Sources in collecting data in the form of primary and secondary data sources, by observation, interview, document review techniques. Theories and concepts used are the Theory of Role, the Theory of Management related to POAC & 6M analysis, the theory of communication, as well as Bhabinkamtibmas Concepts, Promoter Concepts, Radicalisation Concepts, Radicalism Concepts, and Technology Utilisation Concepts. The findings of this study include: (1) Five roles have been implemented, yet still not global; (2) The method and system have not been achieved and the Bhabinkamtibmas program one day visiting five houses is not yet appropriate. Also, the standard of competence and mastery of material radicalism has not yet been met. (3) The supporting factors are organisational structure, support from the other functions, technology development, community support, and cross-agency collaboration. Whilst the inhibiting factors are geographical location, low level of education, limited coordination, high poverty, the spread of radical groups and radical understanding, in line with the weak supervision function of Kasat Binmas, the program of one Bhabinkamtibmas to visits five houses every day, organisational policies, inadequate regulations related to Bhabinkamtibmas, and lack of human resources. Based on the results of the study, the authors propose that competency tests and training programs might be carried out, compile sustainable action plans, technology development, anev of village classification standards, and improvement of funds related to salaries of Bhabinkamtibmas.